Exotic medicinal plants from West Vidarbha region of Maharashtra -III - Rothe*, S.P. (Journal of Ecobiotechnology, 2011)
Present paper deals with the report of 23 exotic medicinal plants collected from various localities from West Vidarbha region of Maharashtra. Some of them are naturalized and now they are the part of our indigenous flora. Tribals and villagers are used them as a medicine and also some are having reputed value. The medicinal values of all plants collected by taking oral interviews with tribals and villagers.